A qualitative content analysis of Al-Hadaf - Nur Shakira Mohd Nasir (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2010)
This study presents a qualitative content analysis study of Al-Hadaf, a quarterly Islamic newsletter published by the Brunei Darussalam State Mufti Department. The newsletter is seen as an authored system of ordering, a noble action with a magnificent aim of converting the Muslim readers into the ideally perfect men (insan-ul-kamil) through its narratives. Theoretically, narrative is a work of social construction which represents the social reality of life-world affairs. It is certainly conditioned by social and in turn creates social influence. This study attempts to examine how Al-Hadaf provides readers with the appropriate Islamic knowledge, as espoused in the 'aqidah, fiqh and tasawuf disciplines, on the relationship with Allah S.W.T the only one and true God, and performing good deeds and not committing evil acts and correlating dunya with akhirah. Qualitative methodology is employed as a framework of the study with the narrative theory as its underpinning theory. Analysis of data is made through the content analysis and semiotic applications, which are then categorized according to the main themes of the al-Qur'an as observed by Izutsu (2004). The main themes were God-man, good-evil and dunya-akhirah. The study found narratives in Al-Hadaf basically revolved around the concept of insan as the created and as a servant to Allah S.W.T., the Creator, whereby he/she needs to acquire the three essential religious disciplines of knowledge, namely, 'aqidah, fiqh and tasawuf and putting them into total religious practices in order to achieve the status of a true knowledgeable Muslim in the real sense of the word.